The underground city: the tourism potential of water and sewage infrastructure: the example of Poland - Piasecki, Adam; Dębczyńska, Klaudia (Bulletin of Geography. Socio-economic Series, 2021)
Industrial tourism and technical facilities are a fast-growing branch of tourism that contains areas of great growth potential. The article deals with one of them. The tourist potential of water and sewage infrastructure in selected Polish cities was analysed and assessed. The study covered 11 cities of diverse socio-economic potentials around the country. For each city, data were collected that had various levels of detail with regard to visitor numbers, tourist types, facilities made available, events and other special celebrations. For supplementary data, unstructured interviews were also conducted with relevant employees identified in businesses. The analysis showed the studied form of tourism to have very high tourism potential. The work focuses on factors and features accounting for its currently low level of development. It is also emphasised that, based on current tourism trends, it should be expected to continue to grow rapidly in the coming years, and thus warrants further research.